Hubungan Pengetahuan, Sikap, dan Ketersediaan Sarana dengan Perilaku Cuci Tangan Pakai Sabun (CTPS) pada Remaja di Lingkungan Sekolah Menengah Atas - Ayunda Budihartono; Yuliaty Anggaraini (Jurnal Kesehatan Sejahtera, 2026)
Handwashing with Soap (HWWS) is a cornerstone in preventing infectious diseases in school environments, particularly among adolescents who exhibit high mobility and intense social interactions. However, the implementation of HWWS in schools is frequently hindered by cognitive, affective, and structural factors. This study aims to analyze the relationship between knowledge, attitudes, and the availability of facilities with HWWS behavior among students at Karya Bakti High School, Selesai District. This quantitative study employed a descriptive cross-sectional approach. The research was conducted at Karya Bakti High School, Selesai District. The study population comprised all students, with a sample size of 132 respondents selected using a simple random sampling technique. Data were gathered via structured questionnaires that had undergone validity and reliability testing, and subsequently analyzed using univariate and bivariate analyses with the Chi-Square test. The findings indicated that the majority of respondents possessed good knowledge (54.5%), demonstrated supportive attitudes (51.5%), and perceived the school's HWWS facilities as adequate (56.1%). Nevertheless, 48.5% of the students still exhibited poor HWWS practices. Statistical tests revealed a significant relationship between knowledge (p = 0.002), attitude (p = 0.001), and the availability of facilities (p < 0.001) with students' HWWS behavior. Students' HWWS behavior is simultaneously influenced by internal factors (knowledge and attitude) and external factors (infrastructure/facilities). The school administration is expected to enhance the supervision and maintenance of sanitation facilities and integrate sustainable health education in a multidimensional manner.